Pengaruh Likuiditas Dan Kredit Macet Terhadap Profitabilitas Pada Perusahaan Perbankan Di Bursa Efek Indonesia - Ananda Serly Nurlita; Immas Nurhayati; M.Imam Sundarta (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to determine the effect of Liquidity and Bad Debt on Profitability. The population used in this study are banking companies listed on the Indonesia Stock Exchange (BEI). The sample selection used the Purposive Sampling method and the companies selected from the criteria were 7 companies for the period 2018-2022, so that the sample used in this study was 35 samples. The data used in this study are secondary data in the form of annual reports and obtained from the Indonesia Stock Exchange (IDX). The analysis technique used in this research is regression with panel data and multiple linear regression using the Eviews 12 program. The results of this study indicate that Liquidity (LDR) has no significant effect on Profitability, Bad Credit (NPL) shows no significant effect on profitability, Liquidity (LDR) and Bad Credit (NPL) have an insignificant effect on Profitability simultaneously.